Dental arches multi-projection system with semantic descriptions - Dias, Diego Roberto Colombo [UNESP]; La Marca, Anthony Ferreira [UNESP]; Vieira, Affonso Moia [UNESP]; Neto, Mario Popolin [UNESP]; Brega, José Remo Ferreira [UNESP]; Guimarães, Marcelo de Paiva [UNESP]; Lauris, José Roberto Pereira (My University, 2010)
This paper presents the development of an multi-projection stereoscopic dental arches application with semantic descriptions. The first section presents the concepts of the used technologies. Applications and examples are demonstrated. Finally, is presented the physical structure and the developed system, where a 3D dental arch is used as a model and can be viewed in multi-projection, thereby, providing greater user's immersion. ©2010 IEEE.
Keywords: Component; Dental arches; Graphics cluster; Multi-projection; Stereoscopic; Semantics; Three dimensional; Arches